Entrepreneurial Action, Unique Assets, and Appropriation Risk: Firms as a Means of Appropriating Profit from Capability Creation - Kaul, Aseem (Organization Science, 2013)
This paper examines organizational boundary choice from an entrepreneurial perspective. Entrepreneurs create new profit opportunities by recombining existing assets into novel combinations based on their subjective judgment under conditions of uncertainty. In doing so, they become vulnerable to ex post appropriation by owners of uniquely complementary assets, especially where ex ante uncertainty translates into ex post causal ambiguity. Firms are a means by which entrepreneurs overcome this problem, maximizing the appropriation of pure profits from their actions. The paper formalizes this insight in an integrative model of entrepreneurial governance choice, highlighting the trade-off between the risk of appropriation and the incremental cost of asset ownership. Comparative statics from this model provide predictions about the conditions under which hierarchical governance will be preferred. In particular, they suggest that firms are preferred where entrepreneurial action results in the creation of combinations of assets that are rare, valuable, and difficult to imitate (i.e., the creation of strategic capabilities). The paper thus contributes to work on the dynamics of capabilities and transaction costs, highlighting the structurally uncertain nature of capability creation and its implications for the theory of the firm.